020 Preoperative clear fluid fasting for children undergoing general anaesthesia. (December 2018) - Morrison, C; Thomas, M; Newton, R; Schindler, E
Abstract : Paediatric anaesthetic guidelines for the management of preoperative fasting of clear fluids are currently 2 hours. The traditional 2 hours clear fluid fasting time was recommended to decrease the risk of pulmonary aspiration and is not in keeping with current literature. It appears that a liberalised clear fluid fasting regime does not affect the incidence of pulmonary aspiration and in those who do aspirate, the sequelae are not usually severe or long-lasting. Fasting for prolonged periods increases thirst and irritability and results in detrimental physiological and metabolic effects. With a 1 hour clear fluid policy, there is no increased risk of pulmonary aspiration. There is less nausea and vomiting, thirst, hunger, and anxiety if allowed a drink closer to surgery. Children appear more comfortable, better behaved and possibly more compliant. In children less than 36 months this has positive physiological and metabolic effects. A local quality improvement project over an 18 month period identified a mean clear fluid fasting time of 6.3 hours a 2 hour clear fasting policy. This project gave all children a drink on arrival and incorporated a prompt in the WHO checklist for children later on the list to be offered a drink up until 1 hour prior to general anaesthesia. The change led to a mean fluid fasting time reduced to 3.1 hours with no increased risk of aspiration or cancellations. This led to a national joint consensus statement supported by the Association of Paediatric Anaesthetists of Great Britain and Ireland, the European Society for Paediatric Anaesthesiology, and L'Association Des Anesthésistes-Réanimateurs Pédiatriques d'Expression Française that unless there is a clear contraindication, it is safe and recommended for all children able to take clear fluids, to be allowed and encouraged to have them up to 1 hour before elective general anaesthesia. Local policy is currently being updated.